Magnetic properties of modified amorfous and nanocrystalline alloys based on Fe and Co - Filippov, B.N.; Potapov, A.P.; Shulika, V.V. (Functional Materials, 2012)
Influence of thermal and thermomagnetic treatments conditions on the magnetic properties and time-temperature stability of amorphous and nanocrystalline alloys based on Fe and Co with additions of Mo, Hf, Zr was studied. It was established that the nanocrystallization in an alternating magnetic field of modified amorphous alloys based on Fe and Co improved significantly their static and dynamic properties and maintained the high thermal stability of the properties. Досліджено вплив умов термічних і термомагнітних обробок на магнітні властивості і температурно-часову стабільність аморфних і нанокристалічних сплавів на основі Fe і Co з домішками Mo, Hf, Zr. Встановлено, що нанокристалізація у змінному магнітному полі модифікованих аморфних сплавів на основі Fe і Co істотно покращує їх статичні і динамічні властивості, зберігаючи високу температурну стабільність властивостей. Исследовано влияние условий термических и термомагнитных обработок на магнитные свойства и температурно-временную стабильность аморфных и нанокристаллических сплавов на основе Fe и Co с добавками Mo, Hf, Zr. Установлено, что нанокристаллизация в переменном магнитном поле модифицированных аморфных сплавов на основе Fe и Co существенно улучшает их статические и динамические свойства, сохраняя высокую температурную стабильность свойств.